Effect of Hyperbaric Oxygen Therapy Combined with Golden Sea Cucumber (Stichopus hermanii Powder to the Level Of Blood Glucose Diabetic Wistar Rat Induced Porphyromonas gingivalis - Rafika Rusydia Darojati; Yoifah Rizka; Syamsulina Revianti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2017)
Background: Diabetes mellitus (DM) is a metabolic disorders characterized by hyperglycemia caused by oxidative stress. Porphyromonas gingivalis (P.g) is a periodontopathogen caused periodontitis exacerbate blood glucose levels (BGL). Hyperbaric oxygen therapy (HBOT) combined with stichopus hermanii (SH) has a role as an antioxidant and antibacterial agent. Purpopse: To analysis effect of HBOT, SH powder and combination of both to the level of blood glucose diabetic Wistar rat induced P.g. Materials and Methods: This study was pre-test-post-test control group design, using 20 male Wistar rat were divided into 5 groups, Group1 (STZ), Group2 (STZ+P.g), Group3 (STZ+P.g+HBOT), Group4 (STZ+P.g+SH powder), Group5 (STZ+P.g+HBO+SH). STZ induction intravenous for 4 days in a row. P.g. induction was exposure 3 times for 4 days. After therapy (7 days), sample blood tail vein of rat were taken for measure BGL by glucometer. Result: Level of blood glucose K1(280.25±88.786)mg/dl, K2(372.25±135.662)mg/dl, K3(249.50±96.652)mg/dl, K4(172.00±82.077)mg/dl, K5(104.75±38.257)mg/dl. Conclusion: Induction of STZ increased the BGL but induction of P.g. cannot exacerbate BGL . HBOT combined with SH powder can reduce BGL in STZ and P.g. induction group.